RATIONALISM OF ISLAMIC RELIGIOUS EDUCATION AND THE AMONG SYSTEM IN SHAPING RELIGIOUS MODERATION AT JUNIOR HIGH SCHOOL TAMANSISWA MEDAN - M. Hasan Ishfi; Nurmawati; Harun Al Rasyid (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the synergy of rationalism of Islamic Religious Education and the Among System in forming religious moderation in Tamansiswa Junior High School Medan. The research uses a qualitative approach with a case study type to deeply understand educational practices that integrate the values of religious rationality and the educational philosophy of Tamansiswa. The research subjects include Islamic Religious Education teachers, school principals, students, and relevant institutional documents. Data were collected through semi-structured interviews, observations, documentation, and descriptive questionnaires, then analyzed using interactive models through data reduction, data presentation, and conclusion drawn. The results of the study show that rationalism in pendidikan agama Islam learning encourages students to understand Islamic teachings critically, reflectively, and contextually through discussion, problem-solving, and case study methods. Meanwhile, the implementation of the Among System through the principles of Ing Ngarso Sung Tulodo, Ing Madyo Mangun Karso, and Tut Wuri Handayani creates a humanistic, dialogical, and democratic learning environment. The integration of these two approaches contributes to the strengthening of religious moderation which is characterized by the development of tolerance, respect for diversity, the ability to dialogue openly, and the tendency to resolve differences through deliberation and peaceful approaches. These findings confirm that the synthesis of rationalism of pendidikan agama Islam and the Among System is an effective educational model in forming a moderate, inclusive, and civilized religious character in the school environment.